Life threating onset of Cardiac Sarcoidosis with mediastinal involvement - Ciuffreda, Marcello; Valenti, Valentina; Manfrè, Giuseppe; Barberi, Antonio; Porzi, Patrizia; Versaci, Francesco; Sarni, Antonella (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
We have described a clinical case with atypical onset of sarcoidosis. A young patient presented to the emergency room with acute heart failure and severe cardiac dysfunction simulating dilated cardiomyopathy or severe myocarditis. Hypoxic respiratory failure refractory to oxygen therapy was treated with steroids. The diagnosis was made by a multidisciplinary team who decided to perform EndoBronchial UltraSound-guided TransBronchial Needle Aspiration (EBUS TBNA) in addition to a cardiac MRI. The result was to obtain, in this case, a prompt therapeutic response in order to preserve the patient cardiac function.